A unified approach to fixed-wing aircraft path following guidance and control. (October 2019) - Kai, J.-M.; Hamel, T.; Samson, C.
Abstract: This paper addresses the path following control problem for scale-model fixed-wing aircraft. Kinematic guidance and dynamic control laws are developed within a single coherent framework that exploits a simple generic model of aerodynamic forces acting on the aircraft and applies to almost all regular 3D paths. The proposed control solutions are derived on the basis of theoretical stability and convergence analyses, and validated via realistic hardware-in-the-loop simulations.